Large-and-Sparse-particle Clouds (LSC): Clouds which are subvisible for space-borne lidar and observable for space-borne cloud radar - Iwasaki, Suginori; Seguchi, Takafumi; Okamoto, Hajime; Sato, Kaori; Katagiri, Shuichiro; Fujiwara, Masatomo; Shibata, Takashi; Tsuboki, Kazuhisa; Ono, Takashi; Sugidachi, Takuji (Polar Science, 2019)
Large-and-Sparse-particle Clouds (LSC), characterized by large particle size (radius > 50 μm) and small number concentration (<104 m−3), were observed with the space-borne lidar, Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP), and with the space-borne 94-GHz cloud profiling radar (CPR). CALIOP was found to be less sensitive to the LSC as compared to CPR because of the particle size distribution of LSC; hence, the cloud type is different from usual ones because CALIOP is generally more sensitive to clouds as compared to CPR when there is no lidar attenuation. An empirical criterion was introduced to identify the LSC from CALIOP and CPR data. The data analysis showed that the LSC tend to appear at high latitudes. The lifetime of LSC would be in the order of hours, because the terminal velocity of LSC particles exceeded 1 km h−1. LSC would not be fallstreak because no cloud existed above. LSC appeared to destroy supercooled clouds (SC) because their cloud top heights were higher as compared to SC, and because LSC and SC did not tend to coexist. Because of their thin optical depth, LSC did not directly impact radiative forcing; however, LSC may indirectly influence radiative forcing through changes in the distribution of SC. journal article